Unveiling Bullying Dynamics in Islamic Boarding Schools for Adolescent Mental Health Promotion - Khamida, Khamida; Fitriyah, Fifi Khoirul; Hidaayah, Nur; Fitriasari, Andikawati; Algristian, Hafid; Soleha, Umdatus; Iskandar (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Islamic boarding schools as educational institutions that teach religious morals as a basis for behavior should be a safe and comfortable place of education for students. There should be no more violence occurring in Islamic boarding schools, but in fact, recently there has been a lot of news about incidents of violence or bullying occurring in Islamic boarding schools. Islamic boarding schools are expected to provide a safe environment for students while fostering religious and moral values. However, incidents of bullying continue to occur within these institutions, highlighting a gap between expected and actual student experiences. Objective: This study aimed to analyze the factors that influence bullying incidents in an Islamic boarding school environment. Methods: A cross-sectional study was conducted at Al-Hidayah Islamic Boarding School, Sidoarjo, involving 109 students selected through simple random sampling (10% of the population). Independent variables included age, gender, school level, length of stay, and peer perception, while the dependent variable was bullying incidence. Data were collected using a validated and reliable questionnaire and analyzed using multiple linear regression at a significance level of 0.05. Results: The results indicated that 68.8% of respondents were in early adolescence (12–16 years), 60.6% were male, and 52.3% had stayed at the boarding school for over 35 months. Additionally, 68.8% of respondents had negative perceptions of their peers. The regression analysis yielded a significance value of 0.004 (p < 0.05) with an R-square of 15.4%, indicating that all independent variables jointly influenced bullying incidents. Conclusion: Age, gender, school level, length of stay in the boarding school, and peer perceptions collectively influence bullying behavior among students. These findings highlight the need for boarding school administrators to implement policies and interventions that address these contributing factors to reduce bullying prevalence.